Empreendedorismo no ensino médio: Explorando o potencial das tecnologias digitais - Veloso, Leonardo Borges (2024)
Digital Information and Communication Technologies (DICTs) are understood as networkconnected technologies, encompassing computers, the internet, videos, software, applications, smartphones, among others. Within the technological, historical, and cultural context, this dissertation addresses the use of DICTs in educational practice, by defining the research problem: how do DICTs contribute to learning in the subject of Entrepreneurship and Innovation in high school? To this end, our general objective was to investigate the use of DICTs in educational practice, specifically in the subject of Entrepreneurship and Innovation in High School. Specifically, we aimed to: investigate how the use of DICTs can support the construction of knowledge in the classroom; recognize a more interactive and engaging learning dynamic; analyze if this practice meets the need for personalization of the student in high school. The methodological approach adopted was qualitative, with a focus group and SWOT analysis. This tool showed that the digital devices provided to schools, especially public schools, are not sufficient to guarantee substantial improvements in the quality of education. The effectiveness of these programs varies, indicating the need for an integrated approach that involves digital skills, the integration of innovative practices, and pedagogical strategies. The research results reveal the widespread adoption of digital resources by teachers, especially in private schools, highlighting films, videos, animations, e-books, among others. However, disparities between public and private schools highlight the need for efforts to promote more equitable digital inclusion. Despite the challenges, the possibilities offered by DICTs represent valuable opportunities to enhance access to knowledge and promote interactive and personalized teaching methods. In this context, the research results served as a solid foundation for the conception and development of the course prototype 'Learn+ Teach+: Technologies and Strategies for Innovative Teachers'.